Pixel-z: Studying Substructure and Stellar Populations in Galaxies out to z~3 using Pixel Colors I. Systematics - Welikala, N; Hopkins, A; Robertson, B; Connolly, A; Tasca, L; Koekemoer, A; Ilbert, O; Bardelli, S; Kneib, J; Zentner, A (2011)
We perform a pixel-by-pixel analysis of 467 galaxies in the GOODS-VIMOS survey to study systematic effects in extracting properties of stellar populations (age, dust, metallicity and SFR) from pixel colors using the pixel-z method. The systematics studied include the effect of the input stellar population synthesis model, passband limitations and differences between individual SED fits to pixels and global SED-fitting to a galaxy's colors. We find that with optical-only colors, the systematic errors due to differences among the models are well constrained. The largest impact on the age and SFR e-folding time estimates in the pixels arises from differences between the Maraston models and the BruzualandCharlot models, when optical colors are used. This results in systematic differences larger than the 2σ uncertainties in over 10 percent of all pixels in the galaxy sample. The effect of restricting the available passbands is more severe. In 26 percent of pixels in the full sample, passband limitations result in systematic biases in the age estimates which are larger than the 2σ uncertainties. Systematic effects from model differences are reexamined using Near-IR colors for a subsample of 46 galaxies in the GOODS-NICMOS survey. For z > 1, the observed optical/NIR colors span the rest frame UV-optical SED, and the use of different models does not significantly bias the estimates of the stellar population parameters compared to using optical-only colors. We then illustrate how pixel-z can be applied robustly to make detailed studies of substructure in high redshift galaxies such as (a) radial gradients of age, SFR, sSFR and dust and (b) the distribution of these properties within subcomponents such as spiral arms and clumps. Finally, we show preliminary results from the CANDELS survey illustrating how the new HST/WFC3 data can be exploited to probe substructure in z~1-3 galaxies.